Analysis of Delays and Time Acceleration Strategies in the Renovation of Grha JST Building - Jujuk Kusumawati; Djoko Subagijo (West Science Interdisciplinary Studies, 2024)
Effective construction project management necessitates adherence to cost, quality, and timeline objectives. However, delays frequently challenge project success, impacting both schedule and budget. This research investigates the causes and consequences of delays within the Grha JST building renovation project, exploring mitigation strategies. Utilizing the Earned Value and Crashing methods, the study analyzes project performance to identify efficient delay management approaches. Recommendations are provided to enhance future project execution and mitigate delays effectively.